Canada's Foreign Policy Dilemmas - Marie Bernard-Meunier (Stiftung Wissenschaft und Politik (SWP), 2005)
Canada plays little part in Europe's Atlantic policy. Yet European and German policy makers should be aware of an emerging debate in the Northern part of North America that could affect Canada's link to Europe and with it European interests. Europeans as yet are not very conscious of the fact that reliable, like-minded, multilateralist partners with enough resources and political will to make a contribution, do not come in such numbers that Canada can be largely ignored. Because of real and acknowledged similarities between Canada and Europe on many foreign and domestic policy issues, Canada has sometimes been referred to as "a North American country with European instincts." But that does not mean that, in comparison to the US, the transatlantic cooperation between Canada and Europe is less problematic and goes on unnurtured. Years of very significant Canadian involvement in the Balkans and major contributions in Afghanistan alongside European troops have not been enough to make Europeans aware of the need to address the unique situation of Canada, for instance in NATO. The question therefore is why should either side do what it does not seem naturally inclined to do, i.e. promote a special relationship. The most obvious first step would be a better inclusion of Canada in the transatlantic dialogue. For that to happen, Canada would have to define convincingly the nature of its added value. It would also have to find within Europe a champion. As a new government in Germany is beginning to define its international role in terms of security, energy and transatlantic relations, this is an aspect that it could do well to consider.
Keywords: 320